Ortopedik Protez ve Ortez Öğrencilerinin Mesleki Seçim Yeterliliği ve Görüşlerinin Değerlendirilmesi - TATAR, YAŞAR (My University, 2021)
Purpose The purposes of the study were to determine the choice capability and opinions of Orthopedic Prosthetics and Orthotics (OPO) students about OPO occupation. Method Within the scope of the study, a survey with multiple-choice questions that include "The Scale of Occupational Choice Capability” was structured with “Google Forms” to assess the student's choice capability about the OPO occupation and forwarded to the universities department representatives. Survey responses were collected between the dates 04.03.2020 and 3.04.2020. Statistical frequencies and percentages of the obtained data were analyzed using Microsoft Office Excel. Results 143 OPO students from 14 different universities in Turkey participated in the study (73.4%female, n: 105; 26.6%male, n: 38) and the mean age of the students was 20.31 years (18-38). 69.3%of the students preferred the OPO department in their top 5 preferences and 54.5%(n: 78) of them preferred to study in other provinces. Among the reasons for preference, the possibility of finding employment easier in the health disciplines (34.3%, n: 49) and want to help orthopedically disabled people (%26.6, n:38) were the most common reasons. 70.7%(n: 101) of the students were satisfied with their department and reported they would prefer this department again if they went back to the past (51.8%, n: 74). According to the answers to the choice capability, 51.8%of students chose the profession because of its status in society and income level (63%), found the profession suitable for their skills (73.5%), and student's physical characteristics (49%). Students reported that they know the opportunities to become advance in the profession (80%), the advantages and disadvantages of the profession, and the working environment (66.5%). It was observed that students do not get informed about the profession from the OPO professionals (50.1%). Conclusion This pilot study showed that OPO students chose the OPO department among their primary preferences knowingly and by researching. It was observed that the students satisfied with their department, and if they want to study again, they might prefer the OPO department. It was noted that the possibility to find employment in the health disciplines is effective on preferences and they were willing about finding employment in state institutions. It was observed that the students did not get informed about the profession from the OPO professionals. Creating a network where candidates and professionals can communicate might be beneficial to increase professional awareness and satisfaction.
The Level of Occupational Choice Capability and Views of Orthopedic Prosthetics and Orthotics Students
Keywords: orthopedic prosthetics and orthotics; occupational education; choice of occupation